DAMPAK AKTIVITAS PELAYANAN PEMERINTAH, YANG TIDAK MENAMBAH NILAI TERHADAP INFLASI (INFLASI SALAH SATU PENGHAMBAT LAJU PERTUMBUHAN EKONOMI) - Sabariah, Etika (www.bsi.ac.id, 2015)
Ineficience time, and apply work that not added value, with flow activities on finished some bisnis, will create high cost and inflantation, with not adapt to building nationalty, because to slacken increase superior competition country on to confront time globlalitation, that it is mean decrease fast growth up economic. That’s why problem inflatation and problem high cost, been solved by government with increase rate SBI, and increase kualitation service to people according to effective and eficience to elimination to appear cost from flow activity that not added value, with method using technology information by government to give information and service to people, matter bisniss, and another that relevance with government. Keywords: Ineficience time, inflatation, fast growth up economic, and technology information government